The high prevalence of asymptomatic SARS-CoV-2 infection reveals the silent spread of COVID-19 - Almadhi, Marwa Ali (Int J Infect Dis, 2021)
PURPOSE: The COVID-19 pandemic has led to over 92 million cases and 1.9 million deaths worldwide since its outbreak. Public health responses have focused on identifying symptomatic individuals to halt spread. However, evidence is accruing that asymptomatic individuals are infectious and contributing to this global pandemic. METHODS: Observational data of 320 index cases and their 1289 positive contacts from the National COVID-19 Database in Bahrain were used to analyze symptoms, infectivity rate and PCR Cycle threshold (Ct) values. RESULTS: No significant difference (p = 1.0) in proportions of symptomatic (n = 160; 50.0%) and asymptomatic index cases (n = 160; 50.0%) were seen; however, SARS-CoV-2 positive contact cases were predominantly asymptomatic (n = 1127, 87.4%). Individuals aged 0−19 years constituted a larger proportion of positive contact cases (20.8%) than index cases (4.7%; p < 0.001). A total of 22% of the positive contacts were infected by symptomatic male index cases aged between 30−39 years. The total numbers of exposed contacts (p = 0.33), infected contacts (p = 0.81) and hence infectivity rate (p = 0.72) were not different between symptomatic and asymptomatic index cases. PCR Ct values were higher in asymptomatic compared to symptomatic index cases (p < 0.001), and higher in asymptomatic compared to symptomatic positive contacts (p < 0.001). No differences between the infectivity rates of index cases with Ct values <30 and values ≥30 were observed (p = 0.13). CONCLUSION: These data reveal that the high asymptomatic incidence of SARS-CoV-2 infection in Bahrain and subsequent positive contacts from an index case were more likely to be asymptomatic, showing the high “silent” risk of transmission and need for comprehensive screening for each positive infection to help halt the ongoing pandemic.